Efek Tipe NbRe Terhadap Sensitivitas Superconducting Single Photon Detector (SSPD) Dalam Penginderaan dan Komunikasi Kuantum - Rahman, Aura Monalisa; Aritonang, Sovian (Rekayasa Material, Manufaktur dan Energi, 2024)
The Single Photon Detector is employed in quantum computing, sensing, and communication technologies. NbRe, a superconductor, exhibits lower noise, energy gap, and minimum energy compared to silicon, resulting in higher sensitivity. NbRe can be found in the form of microstrips and nanostrips. Based on the data, NbRe with a microstrip cross-sectional area will have higher sensitivity and efficiency than NbRe with a nanostrip cross-sectional area. This is because the critical temperature (Tc), minimum energy (Emin), and thickness of NbRe microstrip are smaller than those of nanostrip, while its critical current density is larger. Based on literature review and calculations, it is determined that NbRe microstrip has Tc = 3.08 - 5.23K, Jc = 15.5x10^9 A/m², Emin = 0.017 eV, and a thickness of only 4 nm. In contrast, NbRe nanostrip has Tc = 6.77 K, Jc = 5x10^9 A/m², Emin = 0.28 eV, and a thickness of approximately 14.4 nm.